2018
DOI: 10.4049/jimmunol.1800597
|View full text |Cite
|
Sign up to set email alerts
|

Dicer-2 Regulates Resistance and Maintains Homeostasis against Zika Virus Infection in Drosophila

Abstract: Zika virus (ZIKV) outbreaks pose a massive public health threat in several countries. We have developed an in vivo model to investigate the host-ZIKV interaction in Drosophila. We have found that a strain of ZIKV replicates in wild-type flies without reducing their survival ability. We have shown that ZIKV infection triggers RNA interference, and that mutating Dicer-2, results in enhanced ZIKV load and increased susceptibility to ZIKV infection. Using a flavivirus-specific antibody, we have found that ZIKV is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 127 publications
(186 reference statements)
2
60
2
Order By: Relevance
“…We generated complete transcriptomes from Drosophila wild-type female adult flies infected with the MR766 strain of ZIKV (Harsh et al, 2018;Liu et al, 2018) or injected with PBS (negative/sterile control) (Harsh et al, 2018). We examined gene transcript levels at two timepoints, 4 and 8 days post-injection (dpi) (Fig.…”
Section: Zikv Infection Induces Distinct Transcriptomic Profiles In Dmentioning
confidence: 99%
See 3 more Smart Citations
“…We generated complete transcriptomes from Drosophila wild-type female adult flies infected with the MR766 strain of ZIKV (Harsh et al, 2018;Liu et al, 2018) or injected with PBS (negative/sterile control) (Harsh et al, 2018). We examined gene transcript levels at two timepoints, 4 and 8 days post-injection (dpi) (Fig.…”
Section: Zikv Infection Induces Distinct Transcriptomic Profiles In Dmentioning
confidence: 99%
“…1A). The timepoints were chosen based on the ZIKV load, where 4 dpi corresponds to the early stage of infection, while 8 dpi corresponds to the stage when the infection reaches peak titers (Harsh et al, 2018). The numbers of sequence reads mapped to 96.37% of the D. melanogaster genome ( Fig.…”
Section: Zikv Infection Induces Distinct Transcriptomic Profiles In Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila has been developed as a model of viral infection (Harsh et al, 2018;Liu et al, 2018), and we recently showed that expression of the Zika protein NS4A results in reduced brain size in Drosophila. Strikingly, NS4A expression in Ankle2 A /+ heterozygous animals leads to a more severe phenotype than NS4A expression in a wild type background, and these animals display brain phenotypes that mimic Ankle2 CRIMIC null mutants (Shah et al, 2018).…”
Section: Ns4a Targets the Ankle2 Pathwaymentioning
confidence: 99%